An immuno-wall microdevice exhibits rapid and sensitive detection of IDH1-R132H mutation specific to grade II and III gliomas. Issue 1 (1st January 2016) - Yamamichi, Akane; Kasama, Toshihiro; Ohka, Fumiharu; Suzuki, Hiromichi; Kato, Akira; Motomura, Kazuya; Hirano, Masaki; Ranjit, Melissa; Chalise, Lushun; Kurimoto, Michihiro; Kondo, Goro; Aoki, Kosuke; et al.
Abstract: World Health Organization grade II and III gliomas most frequently occur in the central nervous system (CNS) in adults. Gliomas are not circumscribed; tumor edges are irregular and consist of tumor cells, normal brain tissue, and hyperplastic reactive glial cells. Therefore, the tumors are not fully resectable, resulting in recurrence, malignant progression, and eventual death. Approximately 69–80% of grade II and III gliomas harbor mutations in the isocitrate dehydrogenase 1 gene ( IDH1 ), of which 83–90% are found to be the IDH1-R132H mutation. Detection of the IDH1-R132H mutation should help in the differential diagnosis of grade II and III gliomas from other types of CNS tumors and help determine the boundary between the tumor and normal brain tissue. In this study, we established a highly sensitive antibody-based device, referred to as the immuno-wall, to detect the IDH1-R132H mutation in gliomas. The immuno-wall causes an immunoreaction in microchannels fabricated using a photo-polymerizing polymer. This microdevice enables the analysis of the IDH1 status with a small sample within 15 min with substantially high sensitivity. Our results suggested that 10% content of the IDH1-R132H mutation in a sample of 0.33 μl volume, with 500 ng protein, or from 500 cells is theoretically sufficient for the analysis. The immuno-wall device will enable the rapid and highly sensitive detection of the IDH1-R132H mutation in routine clinical practice. Abstract : UF0001